Using graphs - Easingwood, Nick; Williams, John (ICT and Primary Mathematics, 2004)
If we define a graph simply as a way of presenting or illustrating mathematical information (used in its widest sense), or sets of numbers, in such a way as to make them more easily understood, then we need to make sure that the graph we use does exactly that. Using graphs in the correct way can be great fun, and after producing lots of hard data, children are entitled to feel a sense of satisfaction when this is reproduced in graphical form at the click of a mouse. However, they do need to know why they are doing it, what the graph shows, if it shows the information in the correct way, and whether or not there is something else they should do to the graph, or whether that is the end of the process. It could actually be the beginning, for it is possible that the continued and automatic production of graphs, particularly if done within the confines of ICT ‘lessons’ rather than during active mathematics, may obscure the real use and nature of graphs. For older children, at least, the motivation brought about through the use of ICT should be utilised to rectify this. Although we have given the commonly used definition of a graph, we should better think of it as a diagram which shows a specific relationship between two sets of numbers and what they represent. Because each number comes alternatively from each set, then each pair is said to be ‘ordered’.